Defense response-like reaction associated with an anomaly in Eucalyptus grandis - Fuchs, Maria C. P. [UNESP]; Rossini, Bruno C. [UNESP]; Acencio, Marcio L. [UNESP]; Lemke, Ney [UNESP]; González, Esteban R.; Moricca, Salvatore; Panzavolta, Tiziana; Furtado, Edson L. [UNESP]; Oda, Shinitiro; Marino, Celso L. [UNESP] (Springer Nature, 2022)
Key message: Based on transcriptome and qPCR analysis, a phenotypic abnormality resulting from a Eucalyptus crossing is associated with overexpression of metabolic pathways related to defense responses against biotic and abiotic stress. Abstract: Genetic recombination by outcrossing, a strategy used in improvement programs, can present a low frequency of individuals within progeny with morphological and physiological abnormalities. An abnormality was identified in progeny from a controlled cross of Eucalyptus grandis. Applying RNA-Seq technology to leaf, stem, and root tissue of normal and abnormal seedlings grown under the same greenhouse conditions, we examined global gene expression changes and compared the transcriptional profiles of the two contrasting phenotypes. We also conducted functional enrichment and metabolic pathway analyses. Among the identified differentially expressed genes, most were upregulated in leaf and stem tissues of abnormal plants, with gene ontology (GO) terms associated with 'response to stress', 'response to stimulus', and 'immune system process' categories. Further, in differential gene expression and functional enrichment analyses, we observed overexpression of metabolic pathways related to defense response processes in abnormal plants. Our results suggest that the anomaly is associated with changes in the defense response to biotic and abiotic stresses. As all progeny were grown in a controlled environment and there was no evidence of pathogenic attacks, the defense response in abnormal plants may be due to an autoimmune mechanism caused by genetic incompatibility.
Keywords: Autoimmune syndrome; Defense response; Deleterious phenotype; Differential gene expression; Genetic incompatibility